Cestoda: A New Cestode Circumoncobothrium thapari (A N.SP. Pseudophylidea carus, 1863) from Ophiocephalus stratus, (M.S.), India - Jawale C.J.3, Menkudale D.V1, Ugale B.J.2 and (Journal of Ecobiotechnology, 2010)
The present paper deals with the study of new species of genus Circumoncobothrium thapari n. sp. It differs from all known species of the genus in many characters as in shape of scolex, shape and size of bothria, size, number and position of testes and ovary, size, shape and position of ootype and vitelline gland. --- 1Adarsh College, Omerga Dist. Osmanabad- 413606, (M.S.), India 2S.K.M. Gunjoti Tq. Omerga Dist. Osmanabad - 413613, (M.S.), India 3S.M.P. College, Murum Tq. Omerga Dist. Osmanabad (M.S.), India --- Please Cite This Article As: D.V. Menkudale, B.J. Ugale and C.J. Jawale. 2010. Cestoda: A New Cestode Circumoncobothrium thapari (A N.SP. Pseudophylidea carus, 1863) from Ophiocephalus stratus, (M.S.), India. J. Ecobiotechnol. 2(6):1-3.